ILOLEX 2006 (Geneva : International Labour Orgaisation, 2006)
It is a full-text trilingual database on international labour standa rds. It is a part of a legal information system administered by the IL O's International Labour Standards Department.
Produced by International Labour Standards Department
Keywords: International Labor standards